2017
DOI: 10.3892/etm.2017.4231
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR is a promising novel biomarker in patients with thyroid cancer

Abstract: Thyroid cancer (TC) is the most common endocrine malignancy. Lack of effective early diagnostic tools is one of the clinical obstacles for TC treatment. Thus, enhanced comprehension of the molecular changes in TC tumorigenesis is urgently needed to develop novel strategies for the diagnosis and treatment of TC. Long non-coding RNAs (lncRNAs) manage fundamental biochemical and cellular processes in tumorigenesis and development. One of the best-described lncRNAs, HOX transcript antisense RNA (HOTAIR), functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 23 publications
3
25
0
1
Order By: Relevance
“…HOTAIR was significantly up-regulated in TC compared with adjacent tissues. The results were similar to those detected in TC patients’ plasma, whereas there was almost no HOTAIR expression in the plasma of the healthy volunteers [ 121 ]. HOTAIR susceptibility SNP rs920778 genetic variants (such as TT, TC and CC genotype) are significantly associated with PTC initiation via engaging in the regulation of HOTAIR expression.…”
Section: Introductionsupporting
confidence: 83%
“…HOTAIR was significantly up-regulated in TC compared with adjacent tissues. The results were similar to those detected in TC patients’ plasma, whereas there was almost no HOTAIR expression in the plasma of the healthy volunteers [ 121 ]. HOTAIR susceptibility SNP rs920778 genetic variants (such as TT, TC and CC genotype) are significantly associated with PTC initiation via engaging in the regulation of HOTAIR expression.…”
Section: Introductionsupporting
confidence: 83%
“…The expression of HOTAIR is upregulated in human TC cells compared with normal human thyroid cells. Moreover, knockdown of HOTAIR significantly inhibited cell growth and invasion in TPC-1 and SW579 human TC [46]. …”
Section: Homeobox Transcript Antisense Rnamentioning
confidence: 99%
“…In recent years, increasing evidence suggested that the HOTAIR is highly expressed in a wide array of tumor types. 12,15 Multiple studies have demonstrated that the HOTAIR played significant Figure 5. Increase the HOTAIR levels contributed to rapid growth of PTC by negative regulation of the miR-488-5p expression.…”
Section: Discussionmentioning
confidence: 99%